2013
DOI: 10.1111/jsr.12030
|View full text |Cite
|
Sign up to set email alerts
|

Objective measures of sleep and dim light melatonin onset in adolescents and young adults with delayed sleep phase disorder compared to healthy controls

Abstract: Summary Delayed sleep phase disorder is characterized by a delay in the timing of the major sleep period relative to conventional norms. The sleep period itself has traditionally been described as normal. Nevertheless, it is possible that sleep regulatory mechanism disturbances associated with the disorder may affect sleep duration and/or architecture. Polysomnographic data that may shed light on the issue are scarce. Hence, the aim of this study was to examine polysomnographic measures of sleep in adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 26 publications
5
52
1
Order By: Relevance
“…It was also expected that DLMO would be later during the "saving daylight time" period (summer) than during the "standard time" period (winter) (17). However, in our study, DLMO was not correlated with the chronotype measured by actimetry, whereas previous laboratory sleep studies have shown a robust association between DLMO and time of falling asleep (37,38,39). Our explanation is that DLMO reflected the patients' biological circadian phase that did not correspond to their routine, at-home sleep behavior, suggesting a strong impact of social behavior on sleep timing.…”
Section: Discussioncontrasting
confidence: 86%
“…It was also expected that DLMO would be later during the "saving daylight time" period (summer) than during the "standard time" period (winter) (17). However, in our study, DLMO was not correlated with the chronotype measured by actimetry, whereas previous laboratory sleep studies have shown a robust association between DLMO and time of falling asleep (37,38,39). Our explanation is that DLMO reflected the patients' biological circadian phase that did not correspond to their routine, at-home sleep behavior, suggesting a strong impact of social behavior on sleep timing.…”
Section: Discussioncontrasting
confidence: 86%
“…A lengthy sleep latency (69-124 min) may also contribute to this restricted school night sleep [3,4,8]. The adolescent with DSPD will obtain sleep within normal limits (e.g., 9.5 hrs) during free days (i.e., weekends) [1,2,4,10], as their sleep offset time occurs later in the morning [3], and often into the afternoon [4]. It is likely that the negative consequences of DSPD continue after the school years as young adults with DSPD report significant disruptions to aspects of their work, family, and social life [11].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it should be noted that the exercise of estimating the circadian phase is aimed at providing information upon which to guide treatment but should not be used to form a reliable clinical diagnosis of DSWPD. As reported in previous studies (Micic et al, 2013;Saxvig et al, 2013), there was significant variability in the circadian phase of the current sample, whereby some participants had a circadian phase similar to a normally entrained sleeper. At present, diagnostic criteria for DSWPD is focused on the clinical presentation of delayed sleep-wake timing and the impact of this delay on the daytime functioning of the patient.…”
Section: Discussionmentioning
confidence: 53%
“…sleep onset later than 0200h; based on the mean sleep onset as calculated across all nights reported on the 7-day sleep-wake diary), and were unable to initiate sleep at a preferred earlier time according to the DSWPD-STQ (AASM, 2005). Participants were required to exhibit otherwise good sleep when sleeping at their habitual delayed time (AASM, 2005;Saxvig et al, 2013). Participants were also required to report daytime dysfunction and lifestyle impairments as a result of their sleep pattern (>4 on any subscale of the SDS) and be classified as an evening type (score <42 on the MEQ) to be included.…”
Section: Participants and Screeningmentioning
confidence: 99%